RELEVANSI TINDAK TUTUR DIREKTIF FILM “HARI YANG DIJANJIKAN” SUTRADARA FAJAR BUSTOMI DENGAN PEMBELAJARAN BAHAN AJAR DI SMP - Kristianti, Cyntia Tri; Rahmawati, Laili Etika (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2022)
This research is a type of descriptive qualitative research. The purpose of this research is to describe various types of directive speech in the film Hari that is promised. This study uses data collection techniques in the form of listening, note-taking, and documentation techniques. In addition, the data analysis process uses the agih and matching method. Because both are used to analyze inside and outside the language. The results of this study are that there are six directive utterances found, namely, invitations, requests, requests, orders, advises, and prohibitions. The directive speech that has been analyzed is also relevant to learning Indonesian in junior high school. In accordance with K.D 3.3 and 4.3 in SMP regarding slogan texts. Although it is stated in K.D that there are three texts, however, the focus of this research is the form of relevance to the slogan text in junior high school. In the module there are examples of slogan texts and supporting materials with linguistic features sub-chapters. An example of a slogan text can be taken from fragments of film dialogue that are included in the directive speech. Meanwhile, the linguistic features as supporting material are taken from the types of directive speech, such as invitations, requests, requests, orders, advice, and prohibitions. So it can be concluded that the directive utterances in the film The promised day can be relevant to learning Indonesian in junior high school.Keywords: Basic Competence, Learning, Directive Speech.